THE NEXUS BETWEEN ECONOMIC GROWTH, TRADE OPENNESS AND FOOD SECURITY: AN EMPIRICAL FOR MEDITERRANEAN BASIN COUNTRIES (Third Sector Social Economic Review, 2023)
Food security and the economy are inextricably linked. Ensuring food security will essentially contribute to many protection indicators in order to guarantee healthy safety. When the efficiency of economic growth is used, it may have both positive and negative externalities on food security. The significance of its components on food, food production, and continuously food security, which has the property of disclosing these externalities, is significant. The group weights of economic growth and trade openness on food security are intended from this perspective. The research covers from 1990 to 2021. The Mediterranean basin deposits were performed using empirical analyses. Mediterranean basin nests were preferred due to their climatic conditions, excessive ventilation, and economic potential. Panel data analysis methods included the cross-section dependency test, homogeneity tests, CADF unit root and ECM cointegration tests, and the CCE coefficient estimator. The variables with cross-section dependency are non-stationary at the level and are stationary in the first difference, that is, in I(1). It was determined that the variables defining the model had a cointegration relationship. According to the long-term coefficient estimate results, both economic development and trade openness have positive effects on food security. In other words, economic growth and trade openness improving food security in the aforementioned country group.
Keywords: Economic growth; Food security; Trade openness; ECM cointegration; CCE